A prognostic study of patients with cervical cancer and HIV/AIDS in Bangkok, Thailand - Nintita Sripaiboonkij Thokanit; Pope Kosalaraksa; Pornsuda Jitkasikorn; Tanapol Thonkamdee; Sopit Promchana; Sarikapan Wilailak (Elsevier, 2020)
Cervical cancer is one of the most common cancers of women. In Thailand, the incidence and death rate of cervical cancer are 18.1 and 5.7 per 100,000 women, respectively. Disease progresses faster in patients infected with human immunodeficiency virus (HIV) with acquired immune deficiency syndrome (AIDS). However, limited data are available for Thailand. Here we determined the prevalence of HIV/AIDS and identified factors affecting survival. We reviewed medical records of women infected with HIV with cervical cancer treated at Ramathibodi Hospital from 2007 through 2014. Demographic and clinical data were collected upon diagnosis. We used the Kaplan-Meier method and a Cox proportional hazards model to evaluate the association of overall survival (OS) with risk factors. The mean, median and range of ages at diagnosis of the 1,362 subjects were 53.9 years, 53.0 years and 20-94 years, respectively. The prevalence of HIV/AIDS in patients with cervical cancer was 2.3% and 5-year survival was 61.2%. Multivariable analysis revealed that favourable prognostic factors were a civil servant medical benefit plan and higher education. Advanced cervical cancer was a poor prognostic factor. Prognosis of women with stage III and IV cervical cancer was extremely poor (HR = 7.25 (95%CI: 4.39-11.98)) in stage III and HR = 20.57 (95%CI: 11.59-36.53) in stage IV). The 1-, 3-, and 5-year survival rates of patients with (74.2%, 67.6%, and 63.6%, respectively) or without (87.4%, 71.3% and 63.7%, respectively) HIV/AIDS were not significantly different.